دراسة لحالات سرطان المثانة في محافظة ذي قار العراق للعام 2006 - كاطع خالد (University of Thi-Qar Journal of Science, 2008)
100 samples of patients with bladder cancer who were recordedin general Al-Nassiriya General Hospital (NGH) in 2006 weredetermined in this study.The results indicate that the rate of bladdercancer n male(73%)was more than the rate of bladder cancer infemale(23%). The age periods(50-59years)and(60-69years)were highin bladder cancer compare with other age periods .The bladder cancercases in Al-Nassiriya city were more than the cases in other cities inThi-Qar governorate .The results indicated that there are relationshipbetween bladder cancer and some social and pathogenic cases suchsmoking,coffe intake, Schistosoma haematobium.............etc